Effects of Larch Woolly Adelgid Infestation on Morphological, Histological and Allelochemical Traits of European Larch Needles - Katarzyna Dancewicz; Bożena Kordan; Marta Damszel; Iwona Sergiel; Magdalena Biesaga; Joanna Mroczek; Beata Gabryś (Insects)
The study was carried out to assess the effect of the larch wooly adelgid Adelges laricis Vallot (Hemiptera: Adelgidae) infestation on its secondary host, the European larch Larix decidua Mill. Morphology and anatomy of adelgid-infested needles, and content of defense phenolic compounds including individual flavonoids isorhamnetin, kaempferol, quercetin, rutin, catechin, epicatechin, apigenin, ampelopsin and taxifolin, were analyzed. The amount of total phenols in needles from adelgid-infested twigs of L. decidua increased following the development of the A. laricis population, from the end of April until the end of June. The most abundant among flavonoids were the flavanols, mainly catechin and epicatechin, which predominated in the larch needles during the whole period of adelgid infestation. The content of catechin and epicatechin increased following the increase in the adelgid population number. An increase in content occurred also in flavanonols ampelopsin and taxifolin, while the content of the flavonol kaempferol decreased as the population number of A. laricis increased. The analysis of the anatomical structure of needles showed changes in the shape of the needles, the presence of a thicker layer of epicuticular waxes, and a higher number of mesophyll layers as a result of adelgid feeding.